2022
DOI: 10.1001/jamanetworkopen.2022.7418
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Electric Scooter–Associated Injuries in Finland From 2019 to 2021

Abstract: This cross-sectional study examines the incidence of injuries associated with the use of electric scooters in Finland.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 5 publications
0
8
0
Order By: Relevance
“…Abbreviated injury scale ED Emergency department EMS Emergency medical services ISS Injury Severity Score STRADA The Swedish Traffic Accident Data Acquisition Electric scooters are a fairly new and increasingly popular way of getting around. This has resulted in more electric scooter injuries and hospital admissions and therefore increasing costs for public healthcare [1][2][3][4][5][6][7][8] . Injuries are often minor 9,10 , but head traumas are common and severe traumas and even deaths have been reported 1,4,[11][12][13][14] .…”
Section: Aismentioning
confidence: 99%
“…Abbreviated injury scale ED Emergency department EMS Emergency medical services ISS Injury Severity Score STRADA The Swedish Traffic Accident Data Acquisition Electric scooters are a fairly new and increasingly popular way of getting around. This has resulted in more electric scooter injuries and hospital admissions and therefore increasing costs for public healthcare [1][2][3][4][5][6][7][8] . Injuries are often minor 9,10 , but head traumas are common and severe traumas and even deaths have been reported 1,4,[11][12][13][14] .…”
Section: Aismentioning
confidence: 99%
“…1,2 The most common injury patterns in our population were soft tissue, orthopedic injuries, and head trauma, which is consistent with previously published literature noting fractures and head/facial trauma as leading mechanisms of injury. 2-4 Our study demonstrated that patients who sustained orthopedic injuries were more likely to be admitted to the hospital and require operative intervention. This a similar finding to those reported by Kim et al who noted orthopedic injuries often required admission and/or operative intervention.…”
mentioning
confidence: 75%
“…2,3 In addition, only limited data have been reported about the user database incidences of e-scooter-related injuries. 4,5 Hence, we aimed to examine whether nighttime speed restrictions are associated with the incidence of e-scooter-related injuries.…”
Section: Introductionmentioning
confidence: 99%
“…Several nighttime restrictions have been attempted to decrease the number of injuries, but the outcomes of those restrictions have been evaluated only without the use of user data . In addition, only limited data have been reported about the user database incidences of e-scooter–related injuries . Hence, we aimed to examine whether nighttime speed restrictions are associated with the incidence of e-scooter–related injuries.…”
Section: Introductionmentioning
confidence: 99%